Does interest broaden or narrow attentional scope? - Sung, Billy; Yih, J. (Routledge, 2015)
Theory proposes that interest is a positive emotion that may either broaden attention to facilitate processing of new information, or narrow attention to preserve engagement with new information. To our knowledge, no research has directly examined the effect of interest on attentional scope. Across four experiments, we show that traits associated with the propensity to experience interest—specifically, trait curiosity and internal boredom proneness—are associated with a narrower scope of attention. We also find that, instead of broadening, interest actually narrows attentional scope in comparison to a neutral state and awe. Challenging the conventional notion that all positive emotions broaden cognition and attention, our findings suggest that specific emotions influence attention in ways that extend beyond a general emotional valence effect.